The Effect Of Confining Using Carbon Fiber Reinforced Polymer (CFRP) On The Characteristics Of The Stress-Strain Relationship Of Round Columns In Concrete Retrofit Systems - Edi Santoso,; B. Sri Umniati,; G. Adi Susilo,; Mohd Haziman Wan Ibrahim, (International Journal of Sustainable Construction Engineering and Technology, 2025)
Columns are structural parts whose main function is to resist compressive axial forces. From the results of studies, it is shown that confined concrete parts will increase their ability to withstand compressive axial forces. This research aims to examine the characteristics of the stress-strain relationship in round columns confined with CFRP in a column retrofit system. A total of three short columns with a diameter of 175 mm and a column length of 875 mm were tested with a monotonic axial load until they failed. One column without CFRP restraint and 2 consecutive columns restrained with 1-layer and 2-layer CFRP.  From the research results it was shown that the column compressive strength increased by 54.6% for 1-layer CFRP restraint and 106.2% for 2-layer CFRP restraint. The restraint coefficient k1 value ranges from 2.9 to 3.2 and the k2 value ranges from 19.4 to 24.3. This value is almost the same as the results of previous research, namely k1 = 4.1 and k2 = 20.5 for columns confined with ordinary reinforcement.